Optimization of the Belajar.id Account to Enhance 21st-Century Teacher Competence - Ely Novianti; Erna Yayuk; Ichsan Anshory AM (Jurnal Pedagogi dan Pembelajaran, 2026)
The transformation of 21st century education requires teachers to possess adaptive pedagogical, professional, social, and technological competencies; however, the utilization of learning technology by teachers is still not optimal. This study aims to analyze the optimization of the Belajar.id account in improving teacher competence through independent self-development, technology integration, and the use of digital platforms connected to educational services. This research employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation. Data analysis was conducted through coding, categorization, and theme identification, and its validity was tested through source triangulation. The findings show that the Belajar.id account contributes to improving teacher competence, particularly in accessing independent training, developing innovative teaching materials using Canva for Education, and utilizing the Ruang GTK/PMM platform for reflection and professional development. However, its optimization is still constrained by limited digital literacy, infrastructure, and teachers’ time management. This study concludes that optimizing the Belajar.id account requires school leadership support, habitual use of technology in professional activities, and strengthening sustainable learning communities. The implications of this study indicate that the Belajar.id account has the potential to become a sustainable technology integration model in teacher professional development and serves as a basis for strengthening digital literacy policies and educational transformation in the future era of education.